Hambatan Guru dalam Melaksanakan Prosedur Pengembangan Evaluasi Pembelajaran Bahasa Indonesia Pada Masa Pandemi di SMA Negeri 5 Pekanbaru - Sri Murni; Muhammad Mukhlis (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
This research was motivated by the obstacles found in carrying out evaluation procedures during the pandemic at SMA Negeri 5 Peknabaru. The purpose of the study was to determine the teacher's obstacles in carrying out the procedures for developing an evaluation of Indonesian learning during the pandemic at SMA Negeri 5 Pekabaru. The theory used is the theory of Zainal Arifin with the title "Learning Evaluation". This study uses a phenomenological method with the type of field observation research and a qualitative approach. Data collection techniques using interview and documentation techniques. Obstacles in evaluation planning are the lack of evaluation materials and lack of understanding of applications, obstacles in the implementation of evaluation, namely incomplete online learning facilities, obstacles in monitoring the implementation of evaluation, namely the lack of student monitoring and evaluation planning that is not in accordance with the evaluation implementation, obstacles in data processing, namely sources unstructured data, frequent errors in data processing, obstacles in reporting evaluation results, namely parents who are difficult to contact and obstacles in using the evaluation results, namely the lack of attention of parents to their children and economic factors.